The book of absolutes : a critique of relativism and a defence of universals - Gairdner, William D. (William Douglas), 1940- (McGill-Queen's University Press, 2008)
"Current dogma holds that all cultures and moral values are conditional, nothing human is innate, and Einstein proved that the whole universe is relative. Challenging this position, William Gairdner argues that relativism is not only logically and morally self-defeating but that progress in scientific and intellectual disciplines has actually strengthened the case for absolutes, universals, and constants of nature and human nature." "Gairdner refutes the popular belief in cultural relativism by showing that there are hundreds of well-established cross-cultural human universals. He then discusses the many universals found in physics - as well as Einstein's personal regret at how his work was misinterpreted in the public's eagerness to promote relativism. Gairdner also gives a lively account of the many universals of human biology, including the controversial topic of universal gender differences or "brain sex." He looks at universal concepts of both natural and international law, and ends by discussing language theory. Gairdner shows how philosophers from Nietzsche to Derrida have misused linguistic concepts to justify their relativism, even though a sustained and successful effort by serious scientists and philosophers of language has revealed myriad universals of human language, ranging from language acquisition, to word-order, to Universal Grammar."--Jacket.